Daily sleep quality affects drug craving, partially through indirect associations with positive affect, in patients in treatment for nonmedical use of prescription drugs. (February 2017) - Lydon-Staley, David M.; Cleveland, H. Harrington; Huhn, Andrew S.; Cleveland, Michael J.; Harris, Jonathan; Stankoski, Dean; Deneke, Erin; Meyer, Roger E.; Bunce, Scott C.
Abstract: Objective: Sleep disturbance has been identified as a risk factor for relapse in addiction to a range of substances. The relationship between sleep quality and treatment outcome has received relatively little attention in research on nonmedical use of prescription drugs (NMUPD). This study examined the within-person association between sleep quality and craving in medically detoxified patients in residence for the treatment of NMUPD. Method: Participants ( n = 68) provided daily reports of their sleep quality, negative affect (NA), positive affect (PA), and craving for an average of 9.36 ( SD = 2.99) days. Within-person associations of sleep quality and craving were examined using multilevel modeling. Within-person mediation analyses were used to evaluate the mediating roles of NA and PA in the relationship between sleep quality and craving. Results: Greater cravings were observed on days of lower than usual sleep quality ( γ 10 = − 0.10, p = 0.003). Thirty-one percent of the overall association between sleep quality and craving was explained by PA, such that poorer sleep quality was associated with lower PA and, in turn, lower PA was associated with greater craving. No evidence emerged for an indirect association between sleep quality and craving through NA. Conclusions: Daily fluctuations in sleep quality were associated with fluctuations in craving, an association partially explained by the association between sleep quality and daily PA. These data encourage further research on the relationship between sleep, affect, and craving in NMUPD patients, as well as in patients with other substance use disorders. Highlights: Better than usual sleep quality was associated with lower than usual drug craving. Higher than usual positive affect was associated with lower than usual drug craving. The association between sleep quality and drug craving was partly mediated through positive affect.